Dishevelled-associated antagonist of β-catenin homolog 3 (DACT3) suppresses glioma progression though Notch1 signaling pathway in β-catenin-dependent manner - Jianhe Yue; Jiqin Zhang; Renzheng Huan; Yu Zeng; Ying Tan; Yuan Cheng (Heliyon, 2024)
The disheveled-associated antagonist of β-catenin homolog 3 (DACT3) has been recognized as a tumor suppressor in various cancers. However, the function of DACT3 on glioma malignant progression along with potential molecular mechanisms is poorly clarified. This research aimed to investigate how DACT3 contributes to suppressing the progression of glioma. In our investigation, a pronounced decrease in DACT3 expression was observed in glioma tissues. Through the overexpression of DACT3, we noted a significant suppression in the proliferation, invasion, and migration of glioma cells, while concurrently observing an increase in cell adhesion. Our exploration into the molecular mechanisms revealed that DACT3 executes its tumor-suppressive role by impeding the expression of notch 1 intracellular domain (NICD) and translocating into the nucleus by downregulating the expression of β-catenin. Consequently, this process leads to the suppression of Notch1 signaling. To summarize, our findings reveal the function of DACT3 to inhibit glioma progression via the Notch1 signaling pathway in β-catenin dependent manner. This study stands as the pioneer in examining the role of DACT3 in glioma progression and comprehensively elucidating its molecular mechanisms in glioma development. Therefore, our results suggest that DACT3 holds promise as both a prognostic factor and a potential biomarker for guiding treatment strategies in glioma patients (Graphical Abstract).